2010
DOI: 10.1348/2044-835x.002008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of novel labels on visual processing during infancy

Abstract: The impact of novel labels on visual processing was investigated across two experiments with infants aged between 9 and 21 months. Infants viewed pairs of images across a series of preferential looking trials. On each trial, one image was novel, and the other image had previously been viewed by the infant. Some infants viewed images in silence; other infants viewed images accompanied by novel labels. The pattern of fixations both across and within trials revealed that infants in the labelling condition took lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 40 publications
6
47
0
Order By: Relevance
“…A confluence of ongoing organismic–environmental interactions between term infants’ age and attention, maternal naming frequency, and synchrony use contributed to this longitudinal shift when familiarization length was held constant (Gogate & Maganti, ; also Hunter & Ames, ; Lavoie & Desrochers, ). The shift is consistent with prior findings where the same familiarization length yielded a preference for the familiar stimulus‐event in younger infants, but the novel in older infants in the second year (Houston‐Price & Nakai, ; Mather et al, ). The novelty preference was in part due to greater attention by age on the test (also Mather et al, ); more efficient attentional mechanisms caused the term infants at visit 2 to shift their attention to the novel word–object relations.…”
Section: Discussionsupporting
confidence: 91%
“…A confluence of ongoing organismic–environmental interactions between term infants’ age and attention, maternal naming frequency, and synchrony use contributed to this longitudinal shift when familiarization length was held constant (Gogate & Maganti, ; also Hunter & Ames, ; Lavoie & Desrochers, ). The shift is consistent with prior findings where the same familiarization length yielded a preference for the familiar stimulus‐event in younger infants, but the novel in older infants in the second year (Houston‐Price & Nakai, ; Mather et al, ). The novelty preference was in part due to greater attention by age on the test (also Mather et al, ); more efficient attentional mechanisms caused the term infants at visit 2 to shift their attention to the novel word–object relations.…”
Section: Discussionsupporting
confidence: 91%
“…To answer these two questions, a modified version of the paradigms introduced by Springer and Prinz (2010) and Nation et al (2003) was used, and action prediction was measured via anticipatory eye movements. While some studies found no interfering effects in toddlers aged over 1 year (Robinson & Sloutsky, 2007;Sloutsky & Robinson, 2008), others found that interference could still occur (Mather, Schafer, & Houston-Price, 2011). In Experiment 1, early and late actions (defined according to the AoA of the action labels, Szagun et al, 2009), as well as novel actions, were labeled with a familiar or novel label and compared to a baseline condition where no specific label was presented.…”
Section: Discussionmentioning
confidence: 99%
“…First, the images in the NOUN Database depict multi-part, multi-colored, real threedimensional (3D) objects as opposed to simple geometric shape configurations (e.g., L. B. Smith & Yu, 2008;Wu, Gopnik, Richardson, & Kirkham, 2011) or seemingly animate objects (e.g., Gauthier & Tarr, 1997;Mather, Schafer, & Houston-Price, 2011;Rakison & Poulin-Dubois, 2002). As such, these stimuli are ideal for researchers who need images of naturalistic, complex novel objects to present against images of real 3D objects that are already familiar to participants (e.g., familiar distractors or known competitors).…”
Section: Why Use the Noun Database?mentioning
confidence: 99%